Open access repository-scale propagated nearest neighbor suspect spectral library for untargeted metabolomics - Bittremieux, Wout; Avalon, Nicole E.; Thomas, Sydney P.; Kakhkhorov, Sarvar A.; Aksenov, Alexander A.; Gomes, Paulo Wender P.; Aceves, Christine M.; Caraballo-Rodríguez, Andrés Mauricio; Gauglitz, Julia M.; Gerwick, William H.; Huan, Tao; Jarmusch, Alan K.; et al. (Springer Nature, 2023)
Despite the increasing availability of tandem mass spectrometry (MS/MS) community spectral libraries for untargeted metabolomics over the past decade, the majority of acquired MS/MS spectra remain uninterpreted. To further aid in interpreting unannotated spectra, we created a nearest neighbor suspect spectral library, consisting of 87,916 annotated MS/MS spectra derived from hundreds of millions of MS/MS spectra originating from published untargeted metabolomics experiments. Entries in this library, or “suspects,” were derived from unannotated spectra that could be linked in a molecular network to an annotated spectrum. Annotations were propagated to unknowns based on structural relationships to reference molecules using MS/MS-based spectrum alignment. We demonstrate the broad relevance of the nearest neighbor suspect spectral library through representative examples of propagation-based annotation of acylcarnitines, bacterial and plant natural products, and drug metabolism. Our results also highlight how the library can help to better understand an Alzheimer’s brain phenotype. The nearest neighbor suspect spectral library is openly available for download or for data analysis through the GNPS platform to help investigators hypothesize candidate structures for unknown MS/MS spectra in untargeted metabolomics data.